Analisis Kebugaran Jasmani Siswa Ditinjau melalui Sedentary Lifestyle - Dina Fatmasari; Irma Febriyanti (MAN Insan Cendekia Jambi, 2026)
This study aims to determine the physical fitness of 11th grade students majoring in Film at SMK Negeri 1 Ngasem, Kediri City, in terms of their sedentary lifestyle. This study is a correlational study that applies a quantitative descriptive method with a purposive sampling technique. The sample was determined using total sampling, consisting of 110 students. The research instruments used were the Nusantara Student Fitness Test (TKPN) and the Adolescent Sedentary Activity Questionnaire (ASAQ). Data analysis was performed using descriptive statistics, normality tests, and Spearman's rho correlation test. Based on the results of the Spearman correlation test, a significance value of 0.947 (p > 0.05) with a correlation coefficient of -0.006 was obtained, indicating no significant relationship between sedentary lifestyle and students' physical fitness. This is because students spend 2–5 hours/day on activities such as sitting for long periods of time, using gadgets, playing games, and watching television. It can be concluded that even though the relationship between sedentary lifestyle and physical fitness is not significant, efforts to increase students' physical activity through PJOK learning and extracurricular activities are still needed on an ongoing basis to support the improvement of students' physical fitness.